Disability and Structural Injustice in Miracle in Cell No. 7: A Critical Disability Analysis - Doni Efrizah; Dela Pebriani; Clara Puspita; Purwarno Purwarno (JOURNAL OF LANGUAGE, 2026)
This study examines how intellectual disability and structural injustice are constructed in Miracle in Cell No. 7, directed by Hanung Bramantyo. It aims to analyze the discursive construction of disability and the reproduction of structural discrimination within legal and social contexts. Using a qualitative research design with a critical discourse analysis approach, this study applies Critical Disability Theory to interpret selected dialogues and key scenes that reflect power relations and institutional practices within the narrative. The findings reveal that intellectual disability is constructed as deviance within legal discourse, leading to discursive marginalization and the denial of agency. Discrimination operates structurally through institutional mechanisms such as coercive interrogation, lack of accommodation, and biased legal procedures within the criminal justice system. At the social level, stigma and dominant cultural narratives construct disability as a marker of danger and incompetence, reinforcing exclusion and legitimizing injustice. The novelty of this study lies in highlighting how cinematic narratives reproduce institutionalized ableism across both legal and social domains. It contributes to Critical Disability Studies by emphasizing discrimination as a multidimensional and structurally embedded phenomenon shaped by power relations. Practically, the study underscores the need for disability-inclusive legal frameworks and increased social awareness to promote justice, equality, and dignity for persons with disabilities.